Prospective analysis of the attendance behaviour of the participants of a facilitated support group for patients after allogeneic hematopoietic cell transplantation - Geeck, Karsten; Kreil, Sebastian; Hausmann, Michaela; Hofmann, Wolf-Karsten; Heidenreich, Daniela; Klein, Stefan (Supportive care in cancer, 2024)
Support groups might help survivors of allogeneic hematopoietic cell transplantations (HCT) to cope with medical, psychological, and social challenges. The aim of this project was (1) to establish a facilitated post-HCT support group and (2) to assess the participation behaviour.